Effect of cement kiln dust, lime and fly ash on metal leaching characteristics of oil sands tailings from Alberta, Canada - Mohsen Saeedi; Mahmoud Mahmoud (Diponegoro University, 2021)
The oil sands industry of Alberta generates huge amounts of tailings in a slurry form that typically require up to 40 years to consolidate in very large tailings ponds which are up to 150 m in height. Cement kiln dust (CKD), a byproduct of the ordinary Portland cement manufacturing process, as well as lime and fly ash, collectively referred to as geopolymers, may have the potential to reduce the tailings slurry consolidation period from 40 years, thus affecting the sustainability of such tailings facilities. However, first, it must be demonstrated that these geopolymers will also decrease the metal leaching from thickened tailings (TT) and mature fine tailings (MFT) from the oil sands industry. This study was focused on the use of geopolymers to reduce the environmental impact of TT- and MFT-tailings in the Alberta oil sands industry. Toxicity characteristics leaching procedure (TCLP) and static leaching test (SLT) was used to examine the leaching of metals from tailings, with the SLT test effectively mimicking the leaching process in the tailings ponds environment. Under non-acidic conditions corresponding to the SLT test results, iron concentrations with values of about 530-705 ppm were found to be lower than previous studies on oil sand tailing ponds (2400 ppm). Results showed that geopolymer amendment of TT and MFT significantly reduced the leaching of heavy metals. SLT tests showed that amendment of MFT with 7% CKD decreased Pb, Mn, and Fe leaching, whereas TT-amended with 4% CKD decreased Cu, Pb, Zn, Mn, and Fe. Overall, the CKD amendment of TT showed more than 95% efficiency in the reduction of leaching of all heavy metals. In TCLP tests, TT-amended with 2% FA decreased the leaching of Pb and Ni to acceptable levels with substantial efficiency in reducing the leaching of Fe, Cu, and Zn. TCLP tests also showed that among different amendments, TT-amended with 4% CKD or 2% FA were the most effective proportions for controlling metal leaching from TT, while MFT-amended with 7% lime/FA or 3% CKD were the effective proportions for reducing metal leaching from MFT. Thus, it is deduced that CKD at 3%-4% w/w amendment would work best for reducing leachate levels of both TT and MFT. While amendment of tailings by means of a combination of fly ash and lime also were effective in reducing the leaching of metals, these two geopolymers were not as effective as the CKD amendment.